2017
DOI: 10.1186/s13063-017-2207-x
|View full text |Cite
|
Sign up to set email alerts
|

Central venous Access device SeCurement And Dressing Effectiveness for peripherally inserted central catheters in adult acute hospital patients (CASCADE): a pilot randomised controlled trial

Abstract: BackgroundPeripherally inserted central catheters (PICCs) are commonly used for delivering intravenous therapy. PICC failure is unacceptably high (up to 40%) due to mechanical, infectious and thrombotic complications. Poor securement potentiates all complication types. This randomised controlled trial (RCT) aimed to examine the feasibility of a large RCT of four dressing and securement methods to prevent PICC failure.MethodsThis single-centre pilot RCT included 124 admitted medical/surgical/cancer patients age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
1
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 36 publications
1
53
1
10
Order By: Relevance
“…Original research 25% of central venous catheters [4][5][6] fail prior to treatment completion. High failure rates and associated complications have been recognised internationally for their contribution to patient harm and increased healthcare expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…Original research 25% of central venous catheters [4][5][6] fail prior to treatment completion. High failure rates and associated complications have been recognised internationally for their contribution to patient harm and increased healthcare expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence on the effectiveness of tissue adhesive, or medical-grade superglue, to secure, prevent infection, and promote function of vascular access devices (Bugden et al, 2016, Chan et al, 2017, Edwards et al, 2014. Our data demonstrates that tissue adhesive is associated with increased risk of itch (peripheral devices; HR 6.92) and mechanical skin tears (central devices; HR >100).…”
Section: Discussionmentioning
confidence: 99%
“…The identification of risk factors can then be used to support the development of innovative interventions for appropriate patient groups, to prevent and treat these complications and ensure the efficient use of health resources. Types of studies: Data were extracted from 12 randomised controlled trials (Bugden et al, 2016, Chan et al, 2017, Edwards et al, 2014, Rickard et al, 2012, Webster et al, 2017 and one prospective cohort study completed by the Alliance for Vascular Access Teaching and Research group, and combined into a single database for analysis. The individual studies examined the efficacy of vascular access dressing and securement products (Bugden et al, 2016, Chan et al, 2017, Edwards et al, 2014, Webster et al, 2017, evaluated the effectiveness of routine peripheral vascular access device replacement (Rickard et al, 2012), and observed vascular access-associated management and outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…The trial by Chan et al [68] compared standard care with 3 innovative dressing and securement methods in 121 adult patients receiving acute care. Their findings also showed that securement devices combined with dressings are superior to standard care alone in terms of CRBSI, the catheter failure rate, product costs, and patient and staff satisfaction.…”
Section: Discussionmentioning
confidence: 99%